Investing in the Lusaka South Multi Facility Economic Zone - Mwansa, Stephen; Shaikh, Junaid M.; MUBANGA, Phillip (Advances in Social Sciences Research Journal, 2020)
A Multi Facility Economic Zone (MFEZ) can be described as a Special Economic Zone which can be utilized for export and domestic production purposes by industries operating in the designated economic zone. The MFEZ is characterized by a mixture of several enticing attributes ranging from facilities such as export processing zones, Industrial parks, free trade zones and free ports, among others. Ideally, it is hoped that an MFEZ will kindle economic development in the selected location and consequently contribute to that country’s gross domestic product. It is not uncommon to set up an independent firm to oversee and run the entire administrative affairs of the economic zone on behalf of the owners of the facility. This article is based on a study that was undertaken to assess the performance of the Lusaka South Multi Facility Economic Zone (LS-MFEZ) in Zambia from the time it was established. The research was conducted over a period of eighteen months. This article focuses on two of the objectives of the study that assesses, the effectiveness of the economic zone management firm in stimulating investment in the zone, and the suitability of the economic zone infrastructure as a vehicle for attracting investment in the zone. The research adopted a mixed methods approach using a questionnaire, interviews, and focus group discussions. Interview respondents were selected using snowball sampling. Since the study adopted a mixed research approach with a concurrent triangulation design, data were analysed through a thematic approach for the qualitative component and using descriptive statistics from the Statistical Package for Social Sciences (SPSS) for the quantitative part. The findings show that the zone management firm appears to grapple with some key administrative issues of managing the zone, in addition to inadequate zone infrastructure.